Advance heteroatom dopants nitrogen, boron, sulphur, and phosphorus on carbon dots towards histamine detection in fish sample - Sugito, Siti Febtria Asrini; Hanifah, Nadia Aulia; Nur Aini, Ummi Lathifah; Purwanto, Bambang; Lee, Hwei Voon; Fahmi, Mochamad Zakki (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study introduces heteroatom-doped carbon dots (CDs), namely boron-sulphur (BS-CDs) and nitrogen-phosphorus (NP-CDs), highlighting their potential as optical materials for sensitive histamine detection in sensor applications. Synthesized through facile pyrolysis of citric acid cores with non-metal dopants, resulting in confirmed graphene-like structures and uniform spheres with crystal diameters below 3 nm of BS-CDs and NP-CDs. The optical properties exhibited blue fluorescence, with emission wavelengths of 280 nm (QY 0.08%) and 420 nm (QY 1.72%) for BS-CDs and NP-CDs, respectively. Despite declined fluorescence intensities due to interfering components, both CDs demonstrated low selectivity for histamine, which increased the intensity in its presence. Notably, BS-CDs exhibited superior detectability of histamine at a low concentration of 26.3 ppm compared to 42.8 ppm for NP-CDs. Cytotoxicity studies indicated low toxicity for both CDs, positioning them as promising candidates for further development as histamine detectors